B–Sr–Nd isotopes of Miocene trachyandesites in Lhasa block of southern Tibet: Insights into petrogenesis and crustal reworking - Zhang, Miao-Yan; Hao, Lu-Lu; Wang, Qiang; Qi, Yue; Ma, Lin (Frontiers in Earth Science, 2022)
Adakitic rocks at continental collisional zones have important implications for understanding the mechanism of crustal reworking. The Himalayan–Tibetan orogen, built by India–Asia collision and Indian continental plate subduction, is one of the most prominent Cenozoic continent–continent collision zones, and Cenozoic post-collisional adakitic rocks widely occur in the Lhasa block of southern Tibet. Numerous studies have suggested that the adakitic granitoids in the eastern Lhasa block were derived from partial melting of a juvenile crust and post-collisional mantle-derived ultrapotassic magmas significantly contributed to this crustal reworking by energy and mass transfer. However, the genesis of adakitic rocks in the western Lhasa block remains highly debated, hindering our understanding of crustal reworking in the whole Lhasa block. Here, we report zircon U–Pb age and whole-rock major, trace elemental and Sr–Nd–B isotopic compositions for the Sailipu trachyandesites in the western Lhasa block. Zircon U–Pb dating yields an eruption age of ∼22 Ma. These trachyandesites are high-K calc-alkaline and exhibit intermediate SiO2 (56.9–59.6 wt.%) and low MgO (2.3–4.2 wt.%) contents, low K2O/Na2O (0.8–1.1) ratios, enrichment in light rare earth elements (LREEs), and depletion in heavy REEs (HREEs) with negligible Eu and Sr concentration anomalies. They have high Sr (1080–1593 ppm) and low Y (14.0–26.8 ppm) and Yb (1.08–1.48 ppm) contents, with relatively high Sr/Y (46–95) and La/Yb (46–77) ratios showing adakitic affinities. These Sailipu adakitic rocks display δ11B values of −9.7 to −2.7‰, which are higher than those of mid-ocean ridge basalts (MORBs) but similar to those of arc lavas, indicating contributions from the juvenile crust. However, they have more geochemically enriched Sr–Nd isotopes (87Sr/86Sr(i) = 0.7092–0.7095, εNd(t) = −8.09 to −7.25) than the juvenile crust, indicating contributions from ultrapotassic magmas. Thus, the Sailipu adakitic rocks were likely generated by the interaction between the juvenile lower crust and underplated ultrapotassic magmas. Combined with adakitic magmatism in the eastern Lhasa block, we suggest that magma underplating and subsequent crust–mantle mixing could have been a common and important process that induced the reworking of juvenile crust beneath southern Tibet. This process may be related to the foundering of the subducted Indian continental slab.